2020
DOI: 10.1891/wfccn-d-20-00015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Intensive Care Nurses' Experiences of Caring for Patients With Delirium

Abstract: BackgroundThere is a paucity of studies synthesizing intensive care nurses' experiences of taking care of patients with delirium. A better understanding of nurses' experiences provides an opportunity to identify areas that can be strengthened to improve care.AimTo gain insight into intensive care nurses' experiences of caring for patients with delirium through summarizing the existing qualitative studies in the area.MethodsDatabases of Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In addition, the nurses reported themselves as having been attacked by patients with delirium. Thus, they all agreed that restraining patients with delirium can be necessary, which was comparable to the results of the study by Yang et al 13 synthesizing nursing experiences of ICU delirium care that the decision to restrain or undo restraints might lie on ICU nurses because they observe and interact with patients most closely. However, the ICU nurses reported that this decision is not governed by standardized rules and is based on clinical observation and judgment, similar to the findings of Song and Wu.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, the nurses reported themselves as having been attacked by patients with delirium. Thus, they all agreed that restraining patients with delirium can be necessary, which was comparable to the results of the study by Yang et al 13 synthesizing nursing experiences of ICU delirium care that the decision to restrain or undo restraints might lie on ICU nurses because they observe and interact with patients most closely. However, the ICU nurses reported that this decision is not governed by standardized rules and is based on clinical observation and judgment, similar to the findings of Song and Wu.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
“…Furthermore, Song and Wu 12 systematically reviewed qualitative studies on the experience of Chinese ICU nurses in managing patients with delirium and reported that nurses experienced a mix of positive and negative experiences and that the nurses indicated the nonpharmacological approaches to be prioritized as the positive experiences, rather than the nurses indicating that management measures were difficult to implement; specifically, delirium management plans and practices in ICUs lack standardization and systematization as the negative experiences. Finally, Yang et al 13 conducted the synthesis of different systems for nursing care experiences of ICU delirium patients by 3-stage thematic process from 269 qualitative records; regarding prevention of delirium, reorientation by interacting with patients, improving night sleeping, and early mobilization were included, whereas physical restraints and medical sedation were often used by ICU nurses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, nurses recognize that their efforts to promote night-time sleep appears to prevent delirium. 4 This theory has biological plausibility and provide clinical evidence. For example, sleep disturbance due to increased sleep pressure often results in features of hypoactive delirium, such as daytime somnolence, which is characterized by inattention and altered mood and circadian rhythm.…”
Section: Background and Clinical Questionmentioning
confidence: 97%
“…Anecdotally, critical care nurses maintain that patients with disrupted sleep appear to be more likely to develop delirium. Furthermore, nurses recognize that their efforts to promote night‐time sleep appears to prevent delirium 4 . This theory has biological plausibility and provide clinical evidence.…”
Section: Background and Clinical Questionmentioning
confidence: 99%